Orientation and utility of Information and Communication Technology (ICT) Tools by Agricultural Students and Research Scholars - N. Anandaraja; R. Balasubramaniyam; M. Ramasubramanian; Shibi Sebastian (Journal of Agricultural Extension Management, 2025)
Information and Communication Technology in Agriculture (ICT-A) is an emerging field which combines the advances in agricultural informatics, agricultural development and entrepreneurship to provide better agricultural services, enhanced technology dissemination, and information delivery through various tools such as computer based advisory services (off-line), net based approaches (on-line) and mobile based services. Tamil Nadu Agricultural University (TNAU) is pioneering in the introduction of e-mode of education and teaching-learning process. In view of the ICT initiatives of TNAU, a research study was taken up involving UG, PG and Ph.D. Scholars to understand the level of ICT usage by students and their attitude toward library resources. The results indicate that there is much variation among the scholars on usage of internet facilities, system utility, usage of the computer centre, library resources and on-line examination. Students also expressed the constraints and gave suggestions for effective use of ICT interventions initiated by TNAU